PLURALITY OF SHARIAH BANKING DISPUTE SETTLEMENT METHOD IN INDONESIA - Fatahullah ,SH (Fakultas Hukum Universitas Mataram, 2014)
Shariah banking is a business institution that conducts intermediary function or an agentbetween capital/money-owner and customers requiring capital for financing activities. In theimplementation of that function, potential conflict or dispute with the customer may occur andto overcome such dispute, a set of settlement method is required. The Article 55 of Law Number 21 of 2008 concerning Shariah Banking provides options for dispute settlement namely litigation or religious court and extrajudicial (non-litigation) based on the agreement of both parties. The settlement via the religious court is authorized by the law and set forth under Article 49 of Law Number 3 of 2006 concerning the absolute authority of the religious court to investigate, decide and settle Shariah Banking dispute. Whereas, non-litigation method is also regulated in Law Number 30 of 1999 concerning Arbitration and Dispute Settlement Alternatives whose rulings are final and binding. This model of settlement may be carried out through Deliberation, Banking Mediation or the National Shariah Arbitration Body depending on the contract and agreement entered into by both parties. Principally, religious court does not hold the authority to investigate any case that contain arbitration clause. However, the absolute authority will apply when the parties request it through their actual appearance before the court that it automatically nullifies the arbitration clause.Keywords: Shariah Banking, Dispute, Litigation, Religious Court and Non-Litigation